2021
DOI: 10.3389/fpubh.2021.673959
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Use of PEP and PrEP Among Key Populations Tested in Community Centers in Portugal

Abstract: Background: Pre-exposure prophylaxis (PrEP) and post-exposure prophylaxis (PEP) have been increasingly available in Europe. Due to the high burden of HIV in key populations, these could benefit from their use. In 2016, in Portugal, an open, non-interval, prospective cohort study was established in a network of 26 community-based voluntary HIV/STI counseling and testing centers. Data collected included questions on PEP and PrEP knowledge and use. We aimed to estimate the proportion of PEP and PrEP knowledge and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…According to this systematic review and meta‐analysis, the estimated pooled uptake of HIV/AIDS PEP among healthcare providers in Africa with a random‐effects model was 40.09% (95% CI: 30.14–50.04). This study is similar with study conducted in Pakistan (35.3%) [62,64], but higher than studies conducted in Bhutan (2.1%) [63] and Portugal (1.8%) [64]. This might be due to variations in sociodemographic characteristics, knowledge level and accessibility of the drug.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…According to this systematic review and meta‐analysis, the estimated pooled uptake of HIV/AIDS PEP among healthcare providers in Africa with a random‐effects model was 40.09% (95% CI: 30.14–50.04). This study is similar with study conducted in Pakistan (35.3%) [62,64], but higher than studies conducted in Bhutan (2.1%) [63] and Portugal (1.8%) [64]. This might be due to variations in sociodemographic characteristics, knowledge level and accessibility of the drug.…”
Section: Discussionsupporting
confidence: 88%
“…Funnel plot with pseudo 95% confidence limits F I G U R E 8 Sensitivity analysis of pooled prevalence of knowledge for each study being removed one at a time similar with study in Pakistan (35.3%) [62,64], but higher than studies conducted in Bhutan (2.1%) [63] and Portugal (1.8%) [64]. This might be due to variations in sociodemographic characteristics, knowledge level and accessibility of the drug.…”
Section: Log Plvmentioning
confidence: 99%
“…Seven studies reported higher awareness than 70% among gay men in Israel ( 15 ), young MSM of color in the United States ( 34 ), MSM users of geosocial networking applications in England ( 11 ), non-HIV-positive MSM in Italy ( 32 ), sexually active MSM living with HIV in France ( 35 ), MSM in 22 Sub-Saharan African countries ( 36 ), and among MSM college students in three cities of China ( 37 ). Four studies reported much lower levels of awareness (<40%) among MSM in China ( 33 ); MSM tested in community centers in Portugal ( 38 ) MSM receiving rapid HIV testing in Spain ( 39 ), and among black MSM in the United States ( 13 ). Nine studies reported modest PEP awareness: 41.23% among men engaging in condomless anal sex with men in the United States ( 8 ), 42.5% among MSM in Beijing, China ( 16 ), 46.67% among gay and bisexual men in California ( 40 ), 50% among MSM in Brazil ( 41 ), 56.70% among sexually active MSM in Vancouver, Canada ( 31 ), 57.06% among MSM in Vancouver, Canada ( 42 ), 60.22% among Thai MSM ( 30 ), 60.6% among MSM in four cities of China ( 43 ), and 65.77% among HIV-positive MSM in England ( 44 ).…”
Section: Resultsmentioning
confidence: 99%
“…These factors, which could potentially impede or facilitate participant's awareness of PEP, were conceptually divided into different categories within the individual, social (including partners, families, and communities), and structural domains (health systems and legal factors). In the individual domain, low educational attainment, unemployment, having casual partners, and closeted bisexual were negative factors; high-level education, white race/ethnicity, gay sexual identity, knowing the HIV status of one's self, higher personal sexual altruism, metropolitan resident, higher annual Higher number of partners (11) Higher number of partners (39,42) Having casual partners (35) Higher personal sexual altruism (42) Metropolitan resident (8,42) Greater perceived agency to ask sexual partners' HIV status (42) Older age (31,35,37,40) Higher annual income (16,40,43) Having unprotected anal sex (40) Having sex under the influence of a drug (37,40,41) Younger age (16,32) Using Internet as the main way of meeting partners (39) Social factors Interaction with gay culture (39) Internet and community of MSM (33) Lower levels of HIV stigma (16,32) HIV leadership programming (31) Structural factors Disclosure of one's sexual orientation to general practitioner (11) Greater access to condoms (42) Previous HIV testing (11,15,32,38,43) Previous sexually transmitted infection (STI) diagnosis (38,42) Contact with HIV/AIDS organization…”
Section: Factors Associated With Pep Awarenessmentioning
confidence: 99%
“…Implementation of PrEP free of charge through the national health systems of these two countries began in 2017, with extensive expansion in later years [ 18 ], although few studies have evaluated the success of its implementation [ 27 , 32 , 33 , 34 ] and no survey has focused on studying the population of both countries together, much less comparing them [ 32 , 33 , 34 , 35 ]. Questions still remain whether PrEP can be translated to a successful public health intervention, leading to a decrease in the population-level incidence of HIV, if it is treated only as a local policy, without countries considering the dynamics of the flows of migration and information between countries, for example [ 36 ].…”
Section: Introductionmentioning
confidence: 99%